Mode-2 knowledge production within community-based sustainability projects: Applying textual and thematic analytics to action research conversations - Andrew S. Mitchell (Administrative Sciences, 2020)
Sustainability transition projects (STPs) employ specialist knowledge and learning to lever changes for the communities with which they engage. Research into these forms of organizations often focuses on engagement practices and their relative success or failure to facilitate local transitions toward sustainability. What has attracted comparatively less attention, however, is how STPs develop their own sense of expertise in this role as a broker of Mode-2 knowledge or their own understanding about what it is that they are doing in facilitating community-scale changes. Privileging an emphasis on language-in-use research in organizational theory, this study analyzed the transcriptions of facilitated action research (AR) meetings of a case study STP by applying text mining methods in conjunction with a thematic analysis, the latter exploring insights gained across themes of governance, delivery, networks, challenges, and learning. The findings from these analyses are discussed with reference to how the case study STP staff group construes their work in the domain of sustainability and the generation and acquisition of relevant knowledge and learning in this specialized subsector of community development.
Keywords: 350; organizational learning; Mode-2 knowledge production; language-in-use; text mining; sustainability transition projects